2011
DOI: 10.1177/1368431011403459
|View full text |Cite
|
Sign up to set email alerts
|

Shari’a and legal pluralism in the West

Abstract: Since 9/11, the possibilities for pluralism and tolerance have been severely tested by a discourse of terrorism and security. The development of an intelligent and cosmopolitan understanding between religious communities in Europe and America has been compromised by a range of legal and political responses to terrorism. While the debate about the berqa has clearly indicated the problems relating to Muslim cultural differences, we argue that legal pluralism and in particular the question of Shari’a tribunals ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Scholars of Islam argue the infusion of customs and cultural beliefs into the law, patriarchal bias to legitimise male privilege and politics are causes of erroneous practices of the sharī §ah, in contrast to the spirit of Islam that supports gender equality (al-Hibri 2000, Barlas 2002, Mir-Hosseini 2006, Wadud 1999. Similarly, Turner and Arslan (2011) observe that Islamic law has been varied and dynamic in its interpretation and practice across different eras and societies; some of its original laws are also no longer relevant today (Nasir 1990). The Muslim Marriages Bill presents such a modified interpretation of MPL that would restrict the rights of men while simultaneously allowing women greater legal access and participation in family matters that affect them (Amien 2011).…”
Section: S Abdullah 318mentioning
confidence: 96%
“…Scholars of Islam argue the infusion of customs and cultural beliefs into the law, patriarchal bias to legitimise male privilege and politics are causes of erroneous practices of the sharī §ah, in contrast to the spirit of Islam that supports gender equality (al-Hibri 2000, Barlas 2002, Mir-Hosseini 2006, Wadud 1999. Similarly, Turner and Arslan (2011) observe that Islamic law has been varied and dynamic in its interpretation and practice across different eras and societies; some of its original laws are also no longer relevant today (Nasir 1990). The Muslim Marriages Bill presents such a modified interpretation of MPL that would restrict the rights of men while simultaneously allowing women greater legal access and participation in family matters that affect them (Amien 2011).…”
Section: S Abdullah 318mentioning
confidence: 96%
“…It is possible to see these new ‘legalities’ in terms of legal pluralism and the shift in the conception of the secular in Turkey. The Turkish state has been both regulating its relation to the global economic system and the space of religious affairs, leading to a new secular regime, which promises legal pluralism within the existing secular legal system (Turner and Zengin Arslan, 2011). In this new state approach, the Shari'a is integrated into the economy (through the banking system and Shari'a -based companies), which opens up new forms of and possibilities for global interconnectivity.…”
Section: Religion and Islamic Law In Turkeymentioning
confidence: 99%
“…Many researchers on religious tolerance have conducted in the perspective of local wisdom (Eko & Putranto, 2019;Fadli, 2018;Pajarianto, Pribadi, & Sari, 2022;Purna, 2016;Zuhdi, 2018), religious teaching (Menchik, 2016;Mendus, 2010;Turner & Arslan, 2011), society and country (Brunn & Gilbreath, 2015;J Neusner, 2008;Verkuyten et al, 2014), as well as global politic (Vaezi, 2018). The results of those previous research indicated that the internalization of religious teaching could strengthen tolerance among religious adherents.…”
Section: Introductionmentioning
confidence: 99%